Patchouli Agroindustry Technology In Guo Batu Village, Mandailing Natal Regency, North Sumatera Province - Irmalia Fitri Siregar; Rismawaty; Halimatus Syahdia Hasibuan (Jurnal Riset Perkebunan, 2022)
Achievement level of input use efficiency will determine the success of farmers in achieving maximum production and income from farming and agro patchouli and can compete in the market. The research aimed to analyze system of patchouli agroindustry conducted from production technology, input using, cost, production, income and patchouli agroindustry efficiency and marketing sub-system conducted from channel, marketing organization, cost, profit and marketing efficiency in Guo Batu Village, Mandailing Natal Districk, North Sumatra Province. Census method used in this research with 30 farmers as sampling. The average of agroindustry sub-system production 116,70 kg of patchouli oil per production process, gross income Rp. 64,185,000 and net income Rp. 41,453,091.67. family income Rp. 45,185,076.53 and RCR 2,90. The conclusion is the marketing doesn’t have problem because the farmers sell the patchouli in oil directly to traders with the price Rp. 550,000/kg.